(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
In this paper, I explore the philosophical ideas of Karol Wojtyla, focusing on his anthropology rooted in personalism. Wojtyla emphasized the interconnectedness of individuals, drawing attention to themes like participation, solidarity, and self-giving. His philosophy underscores the complexity of the human person and their inherent relational nature. I analyze his thoughts on the experience of actions and events, the relationship between person and action, and the person’s transcendence through truth and self-gift. This study highlights the inherent dignity of each individual and argues that Wojtyla’s philosophy offers a coherent personalist perspective that merits further exploration.